2017
DOI: 10.1016/j.cell.2017.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Adaptation Establishes Disease Tolerance to Sepsis

Abstract: SummarySepsis is an often lethal syndrome resulting from maladaptive immune and metabolic responses to infection, compromising host homeostasis. Disease tolerance is a defense strategy against infection that preserves host homeostasis without exerting a direct negative impact on pathogens. Here, we demonstrate that induction of the iron-sequestering ferritin H chain (FTH) in response to polymicrobial infections is critical to establish disease tolerance to sepsis. The protective effect of FTH is exerted via a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
238
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(266 citation statements)
references
References 55 publications
11
238
0
2
Order By: Relevance
“…A recent study has suggested that liver iron sequestration regulates blood glucose levels by inducing ferritin to maintain liver gluconeogenesis during sepsis (Weis et al, 2017). Our study provides an alternative explanation: tissue iron sequestration regulates glycemia by inducing acute IR during infection.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has suggested that liver iron sequestration regulates blood glucose levels by inducing ferritin to maintain liver gluconeogenesis during sepsis (Weis et al, 2017). Our study provides an alternative explanation: tissue iron sequestration regulates glycemia by inducing acute IR during infection.…”
Section: Discussionmentioning
confidence: 99%
“…Upon oxidation, extracellular Hb can release its noncovalently bound heme b groups [6–9], generating pro-oxidant labile heme [8,14,15] that acts as a alarmin [16], sensed by pattern recognition receptors, such as Toll like receptor 4 [17] or NACHT, LRR and PYD domains-containing protein 3 (NALP3) [18]. This endows labile heme with pro-inflammatory [1620], vasoactive [21], and cytotoxic [10,2225] effects, while also regulating metabolism [26] and interfering with coagulation [27]. Presumably, these pathophysiologic effects of labile heme contribute critically to the pathogenesis of hemolytic conditions, such as malaria caused upon infection by the protozoan parasites of the genus Plasmodium [6,28], severe sepsis caused by polymicrobial infections [10] or sickle cell disease caused by mutations in the gene encoding the β chain of Hb [21,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…In another mouse study, injection of LPS or infection with S. Typhimurium caused hypoglycaemia when co-administered with a low dose of insulin [53]. A transient reduction in host blood glucose was also reported in a mouse model of polymicrobial bacterial septic infection [115]. A transient reduction in host blood glucose was also reported in a mouse model of polymicrobial bacterial septic infection [115].…”
Section: Turning the Tables On Immune Cells: How Microbial Pathogens mentioning
confidence: 94%
“…Infection can impact on insulin clearance [53] and reduce glucose biosynthesis by gluconeogenesis in the liver [115]. These two scenarios are not mutually exclusive.…”
Section: Turning the Tables On Immune Cells: How Microbial Pathogens mentioning
confidence: 99%
See 1 more Smart Citation